Support Group Communication untuk Kesehatan Mental pada Pasien Covid-19 di Kota Malang - Nilam Wardasari; Nia Ashton Destrity (Program Studi Ilmu Komunikasi, 2023)
Mental health is a major problem for Covid-19 patients who are undergoing isolation. This is feared to have a negative impact on the patient's physical condition. Support groups have the potential to reduce and relieve psychological discomfort for patients and contribute to the recovery of Covid-19 patients. This research aims to identify the communication process and communicative behavior in the Covid-19 patient support group. The research was conducted qualitatively. In-depth interviews were conducted with four Covid-19 survivors who had been hospitalized at the Idjen Boulevard Field Hospital in Malang City. This research shows that when patients first receive a diagnosis of Covid-19, individuals experience stress due to feelings of panic and worry due to insufficient information received. Hospital facilities support the frequency and intensity of interactions between patients. Support groups that have emerged among Covid-19 patients in quarantine homes encourage patients to share stories and experiences with each other. The presence of a psychiatrist at the quarantine home also contributes to reducing the level of stress experienced by Covid-19 patients. This research also confirms that the physical presence and face-to-face communication among patients at the quarantine house has a more significant impact than forms of support from friends and family through mediated communication.